O krzywych eliptycznych - Wilkowski, Andrzej (On Elliptic Curves, 2006)
The work is dedicate to elliptic curves. In the first part one gave arithmetical properties of the group of points of this curve over the finite field. They there make possible the construction of the asymmetric cryptosystem with the public key. The second part talks over the use of elliptic curves in the proof of the Great Fermat Theorem.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2006; nr 1117, s. 188-193